Formulation and Evaluation of Gastroretentive Floating Tablets of Domperidone Maleate - D. Saritha, D. Sathish, Y. Madhusudan Rao (Journal of Applied Pharmaceutical Science)
The low bioavailability (15%) and good solubility of Domperidone Maleate in acidic pH following oral administration favours development of a gastro retentive formulation. Gastroretentive floating matrix tablets of Domperidone Maleate were successfully prepared with hydrophilic polymers like HPMC K4M, HPMC K15M and HPMC K100M. From the Preformulation studies for drug excipients compatibility it was observed that there was no compatability problem with the excipients used in study. The drug release from most of the formulations follows fickian diffusion. From in-vivo X-ray studies, it was clearly observed that the floating tablets showed a gastric residence of nearly 4.5 hrs in fed state.
Keywords: Domperidone Maleate,floating tablets,gastric residence time,gastroretentive drug delivery system.